Targeting Heat Shock Proteins Mitigates Ventilator Induced Diaphragm Muscle Dysfunction in an Age-Dependent Manner - Ogilvie, Hannah; Cacciani, Nicola; Akkad, Hazem; Larsson, Lars (Frontiers in Physiology, 2016)
Intensive care unit (ICU) patients are often overtly subjected to mechanical ventilation and immobilization, which leads to impaired limb and respiratory muscle function. The latter, termed ventilator-induced diaphragm dysfunction (VIDD) has recently been related to compromised heat shock protein (Hsp) activation. The administration of a pharmacological drug BGP-15 acting as a Hsp chaperone co-inducer has been found to partially alleviate VIDD in young rats. Considering that the mean age in the ICU is increasing, we aimed to explore whether the beneficial functional effects are also present in old rats. For that, we exposed young (7-8 months) and old (28-32 months) rats to five-day controlled mechanical ventilation and immobilization with or without systemic BGP-15 administration. We then dissected diaphragm muscles, membrane–permeabilized bundles and evaluated the contractile function at single fiber level. Results confirmed that administration of BGP-15 restored the force-generating capacity of isolated muscle cells from young rats in conjunction with an increased expression of Hsp72. On the other hand, our results highlighted that old rats did not positively respond to the BGP-15 treatment. Therefore, it is of crucial importance to comprehend in more depth the effect of VIDD on diaphragm function and ascertain any further age-related differences.